A Failed Union: How a Lack of Tribal Unity Doomed Black Hawk From the Beginning of 1832 - Schreiber, Nicholas Paul Nelson (My University, 2010)
This essay examines the relationship between Native Americans and whites in the Michigan Territory during Black Hawk's War in 1832. While a dispute over land in the Illinois caused Black Hawk's band of Sauks, Foxes, and Kickapoos to fight against the military of the United States, other tribes did not support him. This essay reveals how these other tribes in the Michigan Territory behaved during the war. While some tensions existed between white settlers and Michigan Territory tribes, there was little desire to aid Black Hawk due to intertribal conflict and the desire for good relations with the United States. Ultimately, a lack of aid caused Black Hawk's forces to lose the war and allowed further white settlement in the Michigan Territory.
Keywords: Whites--Relations with Indians--History--19th century; Black Hawk War, 1832--Participation, Indian; Indians of North America--Michigan--History--19th century